The effect of storage pressure on the mechanical properties of paddy grains. (July 2016) - Cheng, X.D.; Yan, X.J.; Hu, M.Z.
Abstract: To investigate the effect of storage pressure and storage time on the mechanical properties of paddy grains, an experimental study was carried out to determine the mechanical properties of paddy grains compressed at minor axis orientation using the Texture Analyzer. The paddy grains were stored under different pressures and for different time. The results showed that as the storage pressure increased from 0 to 300 kPa, the rupture force of paddy grains stored for 60 days decreased from 81.58 to 73.78 N, the rupture energy from 8.10 to 6.27 mJ, the rupture strain from 0.1392 to 0.1168, the apparent contact modulus of elasticity from 171.32 to 57.68 MPa and the maximum contact stress from 40.84 to 19.11 MPa. All of the mechanical properties of the paddy grains exhibited a linear relationship with storage pressure. As for the paddy grains stored under the pressures of 77, 100, 139, 200 kPa, as the storage time increased from 0 to 60 days, the rupture force of the paddy grains decreased from 81.58 to 79.58 N, 81.58 to 79.12 N, 81.58 to 78.21 N and 81.58 to 76.96 N; the rupture energy decreased from 8.10 to 7.55 mJ, 8.10 to 7.35 mJ, 8.10 to 7.08 mJ and 8.10 to 6.85 mJ; the rupture strain decreased from 0.1392 to 0.1309, 0.1392 to 0.1283, 0.1392 to 0.1257 and 0.1392 to 0.1213. The apparent contact modulus of elasticity decreased from 171.32 to 135.97 MPa, 171.32 to 121.77 MPa, 171.32 to 110.59 MPa and 171.32 to 83.32 MPa; the maximum contact stress decreased from 41.16 to 35.00 MPa, 41.16 to 32.45 MPa, 41.16 to 30.32 MPa and 41.16 to 14.97 MPa, respectively. The results revealed that both storage pressure and storage time have a significant effect on the mechanical properties of paddy grains. Highlights: Rupture force of paddy grain decreased with increasing storage pressure and time. Rupture energy of paddy grain decreased with increasing storage pressure and time. Rupture strain of paddy grain decreased with increasing storage pressure and time. Apparent contact modulus of elasticity decreased with increasing pressure and time. Longterm storage and high storage pressure damage the structure of paddy grain.